STUDI KOMPERATIF KULTUR BELAJAR SISWA PENDIDIKAN AGAMAISLAM TADIKA DI MALAYSIA DAN TK DI INDONESIA - M Iqbal Veriawan Sitepu; Zuliana (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
This study aims to analyze and compare the learning culture of Islamic ReligiousEducation at the Tadika level between Indonesia and Malaysia. This researchuses a comparative qualitative approach with data collection techniques throughparticipatory observation, semi-structured interviews, and documentation at TKAisyiyah Bustanul Athfal 05 Indonesia and Tadika Alfikh Orchard Malaysia.Research informants included school principals, teachers, and parents selectedpurposively. Data analysis used the interactive model of Miles, Huberman, andSaldaña. The results showed that both countries have the main goal of forming thereligious character of early childhood through the integration of Islamic valuessuch as aqidah, worship, and morals, with a holistic approach that emphasizesreligious moderation and daily habituation. The learning culture in Indonesia ismore flexible and community-based (Kurikulum Merdeka PAUD integrated withPancasila national values), focusing on moral habituation and local creativity, whilein Malaysia it is more structured through KSPK with strong governmentintervention, emphasis on discipline, etiquette, and technology, resulting in higherenrollment rates (90% vs 36% in Indonesia). Both countries use teacherexemplarity as a model of Islamic behavior and create conducive religiousenvironments as the main supporting factors in internalizing Islamic values in earlychildhood.